2013
DOI: 10.1167/iovs.13-12079
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Visual Field Defect Severity and Fear of Falling in Primary Open-Angle Glaucoma

Abstract: Among patients with POAG, the severity of visual field defects is associated with fear of falling. (http://www.umin.ac.jp/ctr/index.htm number, UMIN000005574.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…In our multivariable models, we found that FoF was independently associated with being female, white, Medicaid eligible, and having a higher BMI or more medical comorbidities. Prior investigations in older adults with and without VI also detected these associations and reported comparable effect sizes . The association between BMI and FoF in this study suggests that individuals with a higher BMI are more likely to fear falling even when they are no more likely to fall.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our multivariable models, we found that FoF was independently associated with being female, white, Medicaid eligible, and having a higher BMI or more medical comorbidities. Prior investigations in older adults with and without VI also detected these associations and reported comparable effect sizes . The association between BMI and FoF in this study suggests that individuals with a higher BMI are more likely to fear falling even when they are no more likely to fall.…”
Section: Discussionsupporting
confidence: 82%
“…Other studies have also found an association between VI and FoF. [38][39][40] A Japanese clinic-based study found that 23% to 25% of individuals with moderate to severe glaucoma reported FoF (vs 12% of controls and individuals with mild glaucoma). In our study, nearly half of older adults with self-reported VI endorsed FoF.…”
Section: Discussionmentioning
confidence: 97%
“…43,44 Interestingly many patients, even with moderate visual field loss, have a fear of falling and there is good evidence that patients limit their own mobility. [45][46][47] Glaucoma undoubtedly impacts on an individual when visual field loss causes the removal of a driving licence, and several studies have shown that certain glaucomatous visual field defects are not compatible with safe driving. 48,49 Interestingly, it has been demonstrated that UK patients perceive this particular potential outcome of their disease to be as serious to them as the long-term risk of blindness.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 99%
“…Visual function and physical stature are closely related, 21 and visual recovery contributes to mortality and physical performance. Cataract surgery is recognized to both reduce the risk of falls, a serious injury in older adults, [22][23][24][25][26][27][28][29] and improve driving safety 30,31 probably due to the remarkable improvement in visual recognition after surgery.…”
Section: Introductionmentioning
confidence: 99%